Hybridization effects on the out-of-plane electron tunneling properties of monolayers: is h-BN more conductive than graphene? - Zhong, Xiaoliang; Amorim, Rodrigo G.; Rocha, Alexandre R. [UNESP]; Pandey, Ravindra (Iop Publishing Ltd, 2014)
Electron transport properties through multilayers of hexagonal boron nitride (h-BN) sandwiched between gold electrodes is investigated by density functional theory together with the non-equilibrium Green's function method. The calculated results find that despite graphene being a gapless semimetal and h-BN two-dimensional layer being an insulator, the transmission function perpendicular to the atomic layer plane in both systems is nearly identical. The out-of-plane tunnel current is found to be strongly dependent on the interaction at the interface of the device. As a consequence, single layer h-BN coupled with atomically flat weakly interacting metals such as gold may not work as a good dielectric material, but the absence of sharp resonances would probably lead to more stable out-of-plane electronic transport properties compared to graphene.
Keywords: BN monolayer; electron transport; graphene